Brain-wide activation involved in 15 mA transcranial alternating current stimulation in patients with first-episode major depressive disorder - Jie Wang; Qing Xue; Wenfeng Zhao; Huang Wang; Haixia Leng; Mao Peng; Xiukun Jin; Liucen Tan; Keming Gao; Hongxing Wang; Baoquan Min (General Psychiatry)
Background Although 15 mA transcranial alternating current stimulation (tACS) has a therapeutic effect on depression, the activations of brain structures in humans accounting for this tACS configuration remain largely unknown.Aims To investigate which intracranial brain structures are engaged in the tACS at 77.5 Hz and 15 mA, delivered via the forehead and the mastoid electrodes in the human brain.Methods Actual human head models were built using the magnetic resonance imagings of eight outpatient volunteers with drug-naïve, first-episode major depressive disorder and then used to perform the electric field distributions with SimNIBS software.Results The electric field distributions of the sagittal, coronal and axial planes showed that the bilateral frontal lobes, bilateral temporal lobes, hippocampus, cingulate, hypothalamus, thalamus, amygdala, cerebellum and brainstem were visibly stimulated by the 15 mA tACS procedure.Conclusions Brain-wide activation, including the cortex, subcortical structures, cerebellum and brainstem, is involved in the 15 mA tACS intervention for first-episode major depressive disorder. Our results indicate that the simultaneous involvement of multiple brain regions is a possible mechanism for its effectiveness in reducing depressive symptoms.